Visual teaching based on mapping. The screen-image as an educational-artistic artifact (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The construction of images, and the values and functions they can acquire, requires a broader approach that connects visual arts education with our visual culture, which is also shared with scientific culture, where highly mediated images are used. The theoretical review and approach to the agents involved allow us to conduct a more accurate and comprehensive analysis and reflection. This connection rethinks and enriches the role of visual languages in our knowledge. Both the initial assumptions and the paradigm of triangulated convergence in which they are situated (the Art-Science-Technology system), as well as the cases of visual practices that exemplify it, answer the question of which media and languages enable and determine our knowledge and interpretation of the world, without excluding aesthetic languages. This substantially expanded perspective, applied to the field of arts education, broadens the values of images and their relevance. It also transforms both the role of the artist, in a process that is reversed, and the notion of iconicity, once our scale and ocular threshold have been overcome. The study discusses the representational and epistemological dimensions that technically mediated images admit. It recognizes translation and metaphor as sources of knowledge for human understanding.
Keywords: Visual culture; visual epistemology; art education; interface; micrograph